Strategic integrated marketing communications - Percy, Larry (Routledge, 2014)
"With advancing technologies bringing novel, interesting promotional tools to our fingertips, there's never been a more exciting time to be in marketing communications. Nevertheless, the newness of these opportunities brings uncertainty and even potential pitfalls as organisations try to integrate them. Managing these modes is, at its heart, a matter of strategy. A strategic approach to IMC will ensure you brand cohesion, cost effectiveness, a seamless experience of the customer, and a measurable contribution to the goals of the organisation. Now in its second edition, Strategic Integrated Marketing Communications is the only IMC textbook with a strategic perspective to help you meet these goals. New to this edition: New chapters on social media and now to integrate them into your marketing function Robust pedagogy to help reinforce learning and memory Enhanced teaching materials online to help lecturers prepare their courses Brand new real-life case study vignettes An extended section on IMC and planningAs an experienced top-level consultant, Percy writes with practicality, clarity and brevity, making this the perfect textbook of choice for shorter courses and learning professionals. "--Resumé vydavatele
Terminologický slovník
Keywords: marketingová komunikace; strategický management; communication in marketing; strategic planning; monografie; monographs